2022
DOI: 10.1177/00315125221104780
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study: Children’s Perceptions Expressed Through Drawings and Coloring

Abstract: A large body of literature has addressed processes underlying human perception, with some assertions that children do not perceive space or colors in the same way as adults. Since children express themselves easily and acquire knowledge through graphic symbols, when determining psycho-motor maturity and perceptions of a preschool aged children, observers must evaluate their use of non-verbal graphics. Thus, we used young children’s drawings to examine their use of color and spatial perception, as well as to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
0
7
0
1
Order By: Relevance
“…In conclusion, it could be considered that this study identified the very unsafe behavior, and also the non-adopted positive attitudes and perception of road safety behavior among young people in Serbia [41][42][43][44][45]. These conclusions indicate that, in the future, young people must be at the top of the list of road safety problems, and also at the top of the list for future actions regarding road safety in Serbia.…”
mentioning
confidence: 72%
“…In conclusion, it could be considered that this study identified the very unsafe behavior, and also the non-adopted positive attitudes and perception of road safety behavior among young people in Serbia [41][42][43][44][45]. These conclusions indicate that, in the future, young people must be at the top of the list of road safety problems, and also at the top of the list for future actions regarding road safety in Serbia.…”
mentioning
confidence: 72%
“…Emergency rooms could integrate screening processes when these adolescents seek help after an MVC, in order to redirect them to local and public services that offer the psychological help they are seeking. Moreover, as an interesting strand of literature points out, these intervention programs should be integrated with the empowerment of perceptual and motor skills starting from childhood, which have been related to safer driving practices during adolescence and adulthood [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children trained to use computers demonstrate better structural and conceptual knowledge, non-verbal and motor skills, problem-solving abilities, language skills, long-term memory, movement coordination (in drawing), and better intellectual abilities compared to those who did not use technology in learning (Lee et al, 2017;Trifunović et al, 2022a). Perception of space, color, mathematical thinking, creativity, better results on critical thinking tests, and higher levels of motivation are also improved (Papadakis et al, 2016;Trifunović et al, 2022a).…”
Section: Children and New Technologiesmentioning
confidence: 99%